Nutrient utilization of native herbage and oat forage as feed for Tibetan sheep (Ovis aries). (30th August 2022) - Abdelraheem, Nadir; Li, Fuhou; Guo, Penghui; Sun, Yi; Liu, Yang; Cheng, Yunxiang; Cui, Xiongxiong; Tan, Yuhui; Hou, Fujiang
Abstract: Satisfying the animals feed demand from the forage supply by grasslands remains a major challenge in the grassland–livestock ecosystem. To provide an alternative forage sources, this study conducted two feeding trials in the summer of 2015 and 2016 to compare the nutritive value, digestibility and nutrients utilization of native pasture (NH) and oat forage (OT) fed to Tibetan sheep ( Ovis aries ). Twelve Tibetan sheep with a mean body weight of 39.11 ± 3.66 kg in 2015 and 27.97 ± 2.69 kg in 2016 were use in this study. The experiment was 2 (year: 2015 and 2016) by 2 (forage: NH and OT) factorial. Data on proximate analysis, fiber fraction and nutrients digestibility were collected and analyzed using general linear model. However, the crude protein (CP) and water‐soluble carbohydrates contents in OT were higher ( P < .001) than those in NH by 7.81–8.93% and 46.40–47.05%, respectively. In contrast, the neutral detergent fiber (NDF) and acid detergent fiber contents were higher ( P < .001) in NH by 14.28–15.78% and 15.62–18.00%, respectively. The dry matter digestibility coefficient in OT (0.82 in 2015 and 0.79 in 2016) was significantly higher than that in NH (0.68 in both years). In addition, the OT diet had higher ( P < .001) organic matter, NDF and CP digestibilities. Animals fed OT retained significantly more nitrogen (2.66 g/day in 2015 and 1.93 g/day in 2016) than those fed NH (0.96 g/day in 2015 and 0.42 g/day in 2016). The digestible energy and metabolizable energy were higher ( P < .001) in OT than in NH. Our data indicated that Tibetan sheep urinary N excretion increased by 0.726 g with increase of 1 g in the nitrogen intake. Conclusively, the OT had higher nutritive value than NH and could therefore use to satisfy livestock demand and reduce the grazing pressure on grasslands.